Asymmetric [3+2] Photocycloadditions of Cyclopropanes with Alkenes or Alkynes through Visible‐Light Excitation of Catalyst‐Bound Substrates. Issue 19 (10th April 2018) - Huang, Xiaoqiang; Lin, Jiahui; Shen, Tianqi; Harms, Klaus; Marchini, Marianna; Ceroni, Paola; Meggers, Eric
Abstract: The herein reported visible‐light‐activated catalytic asymmetric [3+2] photocycloadditions between cyclopropanes and alkenes or alkynes provide access to chiral cyclopentanes and cyclopentenes, respectively, in 63–99 % yields and with excellent enantioselectivities of up to >99 % ee . The reactions are catalyzed by a single bis‐cyclometalated chiral‐at‐metal rhodium complex (2–8 mol %) which after coordination to the cyclopropane generates the visible‐light‐absorbing complex, lowers the reduction potential of the cyclopropane, and provides the asymmetric induction and overall stereocontrol. Enabled by a mild single‐electron‐transfer reduction of directly photoexcited catalyst/substrate complexes, the presented transformations expand the scope of catalytic asymmetric photocycloadditions to simple mono‐acceptor‐substituted cyclopropanes affording previously inaccessible chiral cyclopentane and cyclopentene derivatives. Abstract : Molecular complexity in a single step : Asymmetric [3+2] photocycloadditions between cyclopropanes and alkenes or alkynes catalyzed by a chiral‐at‐metal rhodium complex are reported. The reactions, enabled by a mild single‐electron reduction of visible‐light‐excited catalyst‐bound substrates, provide access to chiral cyclopentanes and cyclopentenes.